2007
DOI: 10.1590/s0066-782x2007000100002
|View full text |Cite
|
Sign up to set email alerts
|

Acompanhamento clínico de pacientes portadores de cardioversor-desfibrilador implantável

Abstract: Objective: To report appropriate (AT) and inappropriate (IT) ICD therapies in patients with ischemic and nonischemic heart disease, as well as early and late procedure-related complications. Methods:One hundred and fifty-five patients (119 male and 36 female), mean age 47 years (21-88), who underwent ICD implantation between 1994 and March 2003 were analyzed. Patients were divided into the following groups: Group I -Post-AMI patients (n = 80); Group II -Patients with nonischemic heart disease and LV ejection f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 29 publications
0
5
1
5
Order By: Relevance
“…In the present study, the rate of the implantable device events was lower than that reported in the literature, including national studies with patients with BrS, 20 and the one patient with appropriate therapy received it in the first year of follow-up. Nevertheless, the mean 5-year follow-up showed a temporal gain as compared to many similar studies, allowing for the analysis of events in a larger time window - knowing that the risks are continuous throughout life - with the potential advantage of overcoming occasional inaccurate clinical data, manly family history, because the information is patient-dependent and previous data might not be well characterized in the generation immediately before the proband.…”
Section: Discussioncontrasting
confidence: 69%
“…In the present study, the rate of the implantable device events was lower than that reported in the literature, including national studies with patients with BrS, 20 and the one patient with appropriate therapy received it in the first year of follow-up. Nevertheless, the mean 5-year follow-up showed a temporal gain as compared to many similar studies, allowing for the analysis of events in a larger time window - knowing that the risks are continuous throughout life - with the potential advantage of overcoming occasional inaccurate clinical data, manly family history, because the information is patient-dependent and previous data might not be well characterized in the generation immediately before the proband.…”
Section: Discussioncontrasting
confidence: 69%
“… 21 There are only two studies with opposite findings, showing no difference regarding appropriate shock or therapy between chagasic and non-chagasic patients. 23 , 24 The difference in results might be attributed to the small number of chagasic patients included in those two studies (10 and 18, respectively).…”
Section: Discussionmentioning
confidence: 92%
“…Quanto ao acompanhamento clínico de pacientes portadores do CDI no HUCFF, sabe-se que depois do implante do aparelho e a alta hospitalar, que acontece entre 24 a 48 horas após a cirurgia, são realizadas avaliações periódicas desses pacientes, pela equipe médica, a 7, 15 e 30 dias da intervenção. Depois desse primeiro mês, os pacientes são avaliados a cada três meses quanto aos acionamentos do CDI, quando também é acessada a mortalidade global e arrítmica dos portadores do aparelho (FONSECA et al, 2007).…”
Section: Cardiodesfibrilador Implantávelunclassified